Impact of SARS-CoV-2 variants on COVID-19 symptomatology and severity during five waves - Bruno Belmonte Martinelli Gomes; Natasha Nicos Ferreira; Pedro Manoel Marques Garibaldi; Cassia Fernanda Sales de Lima Dias; Letícia Nakamura Silva; Maria Aparecida Alves Leite dos Santos Almeida; Glenda Renata de Moraes; Dimas Tadeu Covas; Simone Kashima; Rodrigo Tocantins Calado; Benedito Antônio Lopes Fonseca; Gustavo Jardim Volpe; et al. (Heliyon)
Background: SARS-CoV-2 variants have distinct features of transmissibility, infectivity, and aggressiveness that may cause different clinical manifestations. A better understanding of the disease presentation and progression could help to outline more precise preventive and treatment frameworks. This study describes the differences in COVID-19 presentation and outcomes across five variant waves. Methods: This prospective cohort was conducted in Serrana, São Paulo State, Brazil. Clinical and demographic data was obtained from June 2020 to December 2022 as part of an enhanced health surveillance system for COVID-19, based on increasing access to diagnostic testing for SARS-CoV-2 and patient follow-up. Individuals were assessed for COVID-19 symptoms and comorbidities. Mild cases were followed up for at least 14 days, and severe cases until discharge or death. Samples were genetically sequenced, and variant waves were determined based on global SARS-CoV-2 variant predominance (>90 % sequenced samples), being as follows: Ancestral, Delta, Gamma, Omicron BA.1, and Omicron BA.2 waves. The relationship between clinical data and disease outcomes was analyzed in each variant wave. Results: Patients infected during the Delta wave were the youngest (36.1 ± 18.2 years, p < 0.001). The proportion of female patients was higher across all waves. Positivity rate, disease severity, and COVID-19-related deaths varied among them. Ageusia and anosmia were related to SARS-CoV-2 positivity during the Ancestral, Gamma, and Delta waves but not in Omicron BA.1 and Omicron BA.2 waves. Diarrhea presented a lower chance of positivity only in Omicron BA.1 and Omicron BA.2. Dyspnea was the most consistent risk factor for severity across all waves. Conclusions: Although patients with COVID-19 from different SARS-CoV-2 variants shared some clinical-epidemiological characteristics, each variant presented distinguishable features related to positivity and severity. This could help to understand the dynamics of COVID-19 variants and update recommendations for clinical practice.